Strategic management practices as a catalyst for SMME performance in the Gauteng province - Tseka, Chidikwane Middah (My University, 2018)
This study explores the prospect of strategic management practices in stimulating SMME performance. In a country were the SMME failure rate is 75% and one of the highest globally, avenues need to be explored to improve the performance and sustainability of SMMEs’. The research aims to investigate the relationship between SMME performance and aspects of strategic management: scanning intensity, locus of planning, planning flexibility, planning horizon and strategic nonfinancial and financial controls. Hypotheses are created based on the performance relationship with each of the strategic management dimensions. The study followed a quantitative research methodology. Data was collected from 99 respondents via a structured questionnaire, the respondents targeted were owners and managers of SMMEs’ in the Gauteng province. The findings of the study supports the hypotheses proving that there is a positive relationship between performance and 5 of the strategic management practices and 1 negative relationship as hypothesised. The practical implications of the study are that owners and managers of SMMEs’ can adopt effective strategic management practices that can lead to performance improvement
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation Wits Business school February 2018
Keywords: Business planning; Strategic planning